Design and PIL implementation of grid-connected photovoltaic system - LOUAIL Chaima; BOUGANDOURA Racha; ENC/ Ismail GHADBANE (University of Msila, 2024)
EN This work presents a simulation model of the electrical part of a grid-connected photovoltaic generator. The model includes a detailed representation of the main components of the system, which are the solar array, boost converter, and grid-connected inverters. An appropriate control for the DC/DC converters has been developed to extract the maximum amount of energy from the photovoltaic generator. The grid-connected inverter transfers the energy drawn from the photovoltaic unit into the grid by maintaining a constant common DC voltage. The modeling and control are carried out using the causal informational graph method. The simulation results using PSIM show the control performance and dynamic behavior of the grid-connected photovoltaic system. Then, the grid-connected system was interfaced with the LAUNCHXL-F28379D board for external simulation . FR Ce travail présente un modèle de simulation de la partie électrique d'un générateur photovoltaïque connecté au réseau. Le modèle inclut une représentation détaillée des principaux composants du système, à savoir le panneau solaire, le convertisseur élévateur et les onduleurs connectés au réseau. Un contrôle approprié des convertisseurs DC/DC a été développé afin d'extraire la quantité maximale d'énergie du générateur photovoltaïque. L'onduleur connecté au réseau transfère l'énergie tirée de l'unité photovoltaïque vers le réseau en maintenant une tension DC commune constante. Les résultats de la simulation utilisant PSIM montrent la performance du contrôle et le comportement dynamique du système photovoltaïque connecté au réseau. Ensuite, le système connecté au réseau a été interfacé avec la carte LAUNCHXL-F28379D pour une simulation externe.